STRATEGI TINDAK TUTUR PERMINTAAN OLEH PENUTUR BAHASA ARAB LAKI-LAKI LIBYA - Aenul Fadilah, Muhammad Ridwan (Center of Middle Eastern Studies (CMES): Jurnal Studi Timur Tengah, 2015)
This research explains the strategies of politeness in requesting expression and utterance politeness level by male speakers of Libya Arabic.The aim of this study is to understand the strategies of request politeness and politeness level. This study using qualitativedescriptive method to analyze the data. This study involved six Libyan male students in six situations. The data collected is using a Discourse Completion Test (DCT). The dataare analyzed according to the model sproposed by Blum Kulka and Elite Olstain(1989) and Rahardi (2005). The findings show that first strategy used by Libyan Arabic male students is direct strategy through the mood derivable 5,5%, explisit performatives 5,5%, and scopestating 22%. Two conventional indirect strategy shows that suggestory formula 14% and query preparatory 53%.